Mobile health interventions on vaccination coverage among children under 5 years of age in Low and Middle-Income countries; a scoping review - Onigbogi, Olanrewaju; Ojo, Omobola Yetunde; Kinnunen, Ulla-Mari; Saranto, Kaija (Frontiers in Public Health, 2025)
ObjectivesIncreased mobile phone use in Low- and Middle-Income countries (LMIC) has led to suggestions that health interventions using mobile phones can help solve some health problems. Vaccination has been shown to be an effective means of improving health outcomes. However, vaccination coverage in many LMIC has been generally low. The aim of this study was to synthesize evidence concerning the context, mechanisms, and outcome elements of mobile health interventions in improving vaccination coverage among children under 5 years of age in LMIC.MethodsA search conducted using PubMed, Web of Science, ScienceDirect, CINAHL, Embase, and the Cochrane library led to 27 studies included in the final analysis out of 357 identified articles.ResultsTwenty-one studies were from Africa, four from Asia and two studies were from Latin America and the Caribbean. Short Message Service (SMS) intervention was used exclusively in 21 studies while six studies used a combination of SMS and phone calls, and one intervention was based only on phone calls.ConclusionThe results from most studies suggest an improved uptake of vaccination with mobile health interventions. However, there is a need for further research to quantify the impact of these interventions and determine the most effective strategies.